Converging and Diverging Governance Mechanisms: The Role of (Dys)Function in Long‐term Inter‐organizational Relationships. (28th November 2017) - Howard, Mickey; Roehrich, Jens K.; Lewis, Michael A.; Squire, Brian
Abstract: This paper explores the dynamic interplay of formal/informal governance mechanisms, in terms of functional and dysfunctional consequences for both sides of the dyad, in long‐term inter‐organizational relationships. Using two longitudinal cases of UK defence sector procurement (warship commissioning) we move beyond notions of complementarity and substitution in governance towards a more nuanced view where the governance mix of inter‐organizational relationships can be convergent or divergent. Our findings, showing that relationships can exhibit functional and dysfunctional behaviour simultaneously, lead us to conclude that mismatches in governance mechanisms can be positive as well as negative. In building a context‐dependent understanding of governance we both summarize the (dys)functions associated with formal and informal governance mechanisms and explore their impact on relationship exchange performance over time.